Evaluasi Atas Pengendalian Intern Penjualan Dalam Kaitannya Dengan Siklus Pendapatan Pada PT. Hotel Properti Internasional (HPI) "BeeOutbound" - Hasibuan, David; Marlina, Tri; Rinjani, Mayang Eryan (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
The objective of this study was to determine the intemal control ofsale of PT HPI (dept. BeeOutbound), analyse PT HPI (dept. BeeOutbound) revenue cycle and to evaluate the internal control of sales in relation with the revenue cycle at PT. Hotel Properti Intemasional (HPI) (Dept. BeeOutbound). The method used in this script is a descriptive method, and the data collection procedure is done in two ways, namely library research to obtain secondary data, and field research to obtain primary data from the company. For the field research, the author uses three techniques namely are interview, observation, and survey documents. The results of the evaluation of intemal control of sales in relation with the revenue cycle, is that the method of sale applied by PT. HPI (dept. BeeOutbound) is a cash sale. In this case it can be described that intemal control of cash sales at PT. HPI (dept. BeeOutbound) has not been conducted in accordance with proper intemal controls as still occur germinating tasks performed by the administration and accounting. Although the outline of the internal control of cash sales in the revenue cycle is good enough and it is also supported by activities that always meeting regularly performed once a week to monitor the performance of the company and also the company's financial condition. When linked with the results of the evaluation of internal control of sale in relation with the revenue cycle then the PT. HPI has not met these requirements ofgood internal control. Keywords: Internal control of sale, revenue cycle.